Animals in danger : trying to save our wildlife - National Geographic Society (U.S.); Winston, Peggy D. ([Washington] : National Geographic Society, 1978)
Brief text and pictures describe the habits and behavior of a variety of endangered animals. Cartoons explain some of the efforts being made to protect these animals.
Keywords: Rare animals -- Juvenile literature; Wildlife conservation -- Juvenile literature; Rare animals; Wildlife conservation